جماليات الفضاء الصحراوي في المجموعة القصصية:"حائط رحمونة لعبد الله كروم"أنموذجا. - (:unkn) unknown (جامعة الوادي - University of Eloued, 2023)
الملخص: تناولت هذه الدراسة المجموعة القصصية " حائط رحمونة" للقاص عبد الله كروم حيث يطرح القاص إشكالية تناسي الإنسان الصحراوي لعاداته وتقاليده ، وتخليه على البيت الطيني الذي هو رمز الهوية ، كما تتناول هذه الدراسة جماليات الفضاء الصحراوي وأبعاده الدلالية والثقافية والذي تجلى في التفاصيل المهمشة كالحائط والفقارة في الصحراء نفسها في الواحة بزخمها الثقافي والدلالي في المرأة الصحراوية المكافحة والمتفائلة . Abstract : This study deals with the collection of stories "The Wall of Rahmouna" by the storyteller Abdullah Karroum, where the narrator presents the problem of the desert man's forgetting of his customs and traditions, and abandoning him to the mud house, which is a symbol of identity. The desert itself is in the oasis with its cultural and semantic momentum in the struggling and optimistic desert woman.
Keywords: الصحراء ، الهوية ، الفضاء ، حائط رحمونة ، العادات والتقاليد ، الإنسان; desert, identity, space, Rahmouna wall, customs and traditions, man.